PROFESSIONAL GUIDANCE AS A SOCIAL-PEDAGOGICAL PROCESS (Conference Zone, 2022)
Vocational guidance is a system of evidence-based activities aimed at preparing young people to choose a profession, taking into account the characteristics of a person and the socio-economic situation in the labor market, helping young people to determine their professional self-determination and employment.